2017
DOI: 10.5603/njo.2016.0080
|View full text |Cite
|
Sign up to set email alerts
|

Breast self-exams in a group of women participating in mammography screening Elżbieta Garwacka-Czachor, Adam Maciejczyk

Abstract: Introduction.A key role in the struggle against breast cancer is played by secondary prevention, which includes breast self-exams, clinical tests, and mammography screening. The purpose of the study was to analyze the impact of age, education, and selected breast cancer risk factors on the frequency with which women participating in the mammography screening program perform breast self-exams. Material and methods. The study group consisted of 32,626 women aged 50-69, enrolled in the Early Breast Cancer Detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
1
0
1
Order By: Relevance
“…tion [17]. In fact, over 90% of breast cancers can be detected by this method [18]. In the present study, the obtained results were satisfying, as relatively low number of students claimed not knowing this method.…”
Section: źSources Of Knowledge About Breast Cancer Preventionsupporting
confidence: 72%
See 1 more Smart Citation
“…tion [17]. In fact, over 90% of breast cancers can be detected by this method [18]. In the present study, the obtained results were satisfying, as relatively low number of students claimed not knowing this method.…”
Section: źSources Of Knowledge About Breast Cancer Preventionsupporting
confidence: 72%
“…Jest to najbardziej dostępna, łatwa do wykonania i skuteczna metoda [17]. Ponad 90% zmian nowotworowych wykrywanych jest właśnie przez własnoręczne badanie piersi [18]. W prezentowanym badaniu otrzymano zadowalające wyniki, ponieważ stosunkowo mało studentów uznało, że nie zna tej metody.…”
Section: Dyskusjaunclassified
“…The reverse of this phenomenon was observed in the study by Garwacka-Czachor et al In this study conducted among 32 626 women aged from 50-69 years old, it was observed that 14% (4 512) of women performed breast self-examination once a month. Moreover, there was a correlation between level of education and frequency of breast self-examination -the higher education a woman had, the more often she performed self-examination [27].…”
Section: Discussionmentioning
confidence: 99%